Respon 10 Varietas Krisan (Dendranthema grandiflora Tzelev) terhadap Dua Aplikasi Pemupukan di Lahan Terbuka - Rahmawati, Ika; Winarto, Budi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTCultivation of the chrysanthemum is usually carried out under the plastic-house to produce high quality flowers, but in some areas such as in Karo (North Sumatera), farmers have grown the plant in the open field using selected varieties for the same purpose. The study was aimed to assess responses of ten varieties of chrysanthemum toward two applications methods of fertilizer which was carried out in open-field at Segunung Experimental Garden, Indonesian Ornamental Crops Research Institute (IOCRI) from July till December 2011. The experiment was arranged in a split-plot design with three replications. The main plot was ten chrysanthemum varieties of Besar Kuning, Merah Hati and Sakuntala; Besar Bandung, Berlian Putih, Matahari Kuning, Mata Kucing, Mata Dewa, Swarna Kencana and Puspita Nusantara. The subplot were  two fertilizer applications methods, Karo and Balithi. Karo: manure 100 kg m-2 and 50 kg m-2 (in month 2), urea 30 g m-2 (in month 3) and Balithi: manure 20 ton ha-1,  urea 200 kg ha-1, 350  kg KCl ha-1 dan 300 kg SP-36 ha-1, supplementary 1.5 g urea m-2, 6 g KNO3 dan 6 g SP-36 m-2. Both methods of  applications can be applied to open field cultivation. Method of fertilizer application significantly affected stem diameter, intensity of disease infection and the time of flower initiation. The Balithi’s fertilizer application significantly reduced the intensity of rust disease on chrysanthemum, while Karo’s fertilizer application significantly increased stem diameter.Keywords: Chrysanthemum, open-field, two fertilization application, stem diameter, rust disease